Substance use disorders: leading the road to recovery. Issue 7 (23rd June 2020) - Dennis, Emily K.; Garneau-Tsodikova, Sylvie
Abstract : Substance use disorders are diseases of the brain that create a dependency to various drugs. This opinion article provides an overview of the treatments available for these disorders and a perspective of what remains to be done on the road to recovery. Abstract : Substance use disorders are diseases of the brain that create a dependency on drug(s), either prescription or illicit. These diseases affect millions of people worldwide, yet, there are few treatments that can help patients in the long term. This opinion piece looks at strategies researchers and institutes are taking to help find treatments as well as at new therapies in clinical trials. It provides an outlook on how a changing public perspective of these diseases can ultimately lead to a brighter outlook for substance use disorder treatments.